Efektifitas Terapi Kelompok Cognitive Behaviour Therapy untuk Menurunkan Kecemasan Sosial pada Dewasa Gagap - Erizza Farizan Adani; Afif Kurniawan (Universitas Kristen Maranatha, 2023)
Adults seeking treatment for stuttering presented a comorbid diagnosis of social anxiety. The development of social anxiety may be related to negative conditioning experiences from an early age regarding people’s responses when reacting to stuttering such as confusion, interrupting, mocking, distancing, or ignoring stuttering speech. Repeated exposure to negative social reactions causes people who stutter to form beliefs that negative evaluations will occur in all social situations. The high level of social anxiety is more concerning given the data showing that increased anxiety can increase the frequency of stuttering. The purpose of group therapy with Cognitive Behavior Therapy is to reduce social anxiety and negative thoughts related to social anxiety in stuttering adults. The method used is a quantitative method supported by qualitative data from interviews. The results showed a decrease in social anxiety and negative thoughts in the group’s average score after undergoing therapy. In addition, there were changes in behavior, thoughts, and feelings after the session as evidenced from the follow-up interview a month after the end of therapy.